Striving for a Conceptual Understanding of Mathematics for All Students (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
The process of learning to learn mathematics starts with an educational approach of allowing the students to discover mathematical concepts. This discovery enforces conceptual understanding in mathematics and eliminates the need for rote memorization of procedures and formulas. For this teaching style to be successful, educators must be willing give students control of their own learning. By allowing students to process mathematical concepts individually, teachers help them make real-life connections and build their knowledge of mathematics collectively and across all grades levels.